The Geography of Beer 2014
DOI: 10.1007/978-94-007-7787-3_13
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquity of Good Taste: A Spatial Analysis of the Craft Brewing Industry in the United States

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…We also controlled for the census division in which the tract is located, as defined by the US Census Bureau (2000). As we described earlier, existing research has shown an uneven geographic distribution of craft beer, with far greater prevalence in the western US and far less prevalence in the southeastern portion of the country (Baginski and Bell 2011;McLaughlin, Reid, and Moore 2014;Grohmann 2015). Independent variables in the models are cross-sectional and paired together: one member of the pair measures change over time while the other measures the value in the base year.…”
Section: Identifying Neighborhood Changementioning
confidence: 82%
“…We also controlled for the census division in which the tract is located, as defined by the US Census Bureau (2000). As we described earlier, existing research has shown an uneven geographic distribution of craft beer, with far greater prevalence in the western US and far less prevalence in the southeastern portion of the country (Baginski and Bell 2011;McLaughlin, Reid, and Moore 2014;Grohmann 2015). Independent variables in the models are cross-sectional and paired together: one member of the pair measures change over time while the other measures the value in the base year.…”
Section: Identifying Neighborhood Changementioning
confidence: 82%
“…Despite being in the southeastern region of the U.S., which has been lagging in terms of the number of craft breweries per capita due to historical, regulatory, and cultural factors (Baginski & Bell, 2011), Charlotte (together with other urban areas in North Carolina) has a vibrant and growing craft brewing scene (McLaughlin, Reid, & Moore, 2014). Despite being in the southeastern region of the U.S., which has been lagging in terms of the number of craft breweries per capita due to historical, regulatory, and cultural factors (Baginski & Bell, 2011), Charlotte (together with other urban areas in North Carolina) has a vibrant and growing craft brewing scene (McLaughlin, Reid, & Moore, 2014).…”
Section: Craft Brewing In Charlottementioning
confidence: 99%
“…Charlotte is the most populous city in the state of North Carolina with a population of 859,035 in 2017, a 16.8% increase since 2010 (United States Census Bureau, 2019). Despite being in the southeastern region of the U.S., which has been lagging in terms of the number of craft breweries per capita due to historical, regulatory, and cultural factors (Baginski & Bell, 2011), Charlotte (together with other urban areas in North Carolina) has a vibrant and growing craft brewing scene (McLaughlin, Reid, & Moore, 2014). As of June 2018, there were 30 breweries operating in Mecklenburg County where Charlotte is the county seat.…”
Section: Craft Brewing In Charlottementioning
confidence: 99%
“…Commercial craft brewing is now a global phenomenon (Verive, 2015). Several reports and academic studies completed in the last few years highlight the growth of the industry, for instance, in the United States (e.g., Baginski and Bell, 2011;Gnauck et al, 2014;McLaughlin et al, 2014;Reid et al, 2014). Reflecting the growth taking place in the United States, Australia's craft brewing industry has experienced remarkable development.…”
Section: The Emerging Craft Brewing Industrymentioning
confidence: 99%